Digital Economy and Development Opportunities in Developing Countries - Jhonny Zainal Abidin; Darwati Susilastuti (Siber Nusantara of Economic and Finance Review, 2026)
This research examines the role of the digital economy as a catalyst for economic development in developing countries. The research method employs a qualitative approach with secondary data analysis from various sources. Research results show that Indonesia's digital economy grew 13% from 2023 to 2024, reaching USD 90 billion. The e-commerce sector dominates with a contribution of USD 65 billion, while the online transportation and food delivery services sector grew 13% to USD 9 billion. Digital divide remains a major issue, with 49% of Indonesian adults still lacking internet access. The research found that digital transformation requires infrastructure improvement, human resource development, and adaptive regulation. This study concludes that the digital economy provides great opportunities for economic development in developing countries but requires a structured strategy to overcome various obstacles.